Prevalence, risk and severity of SARS-CoV-2 infections in psoriasis patients receiving conventional systemic, biologic or topical treatment during the COVID-19 pandemic: a cross-sectional cohort study (PsoCOVID) - Kevin V. Kwee; Jean-Luc Murk; Qiqi Yin; M. Birgitte Visch; Linda Davidson; Elke M. G. J. de Jong; Juul M. P. A. van den Reek; Milan Tjioe (Taylor & Francis Group, 2023)
Background The risk of SARS-CoV-2 infection does not appear to be increased for psoriasis patients using biologics compared to those on other treatments, but evidence is still limited. Objectives (1) to estimate the prevalence of SARS-CoV-2 infection in patients with psoriasis, (2) to compare SARS-CoV-2 infection rates for different psoriasis treatments groups (biologic vs. systemic conventional vs. topical therapy) corrected for confounders and (3) to describe patients with severe COVID-19 for all treatment groups. Methods In this cross-sectional cohort study all patients received a questionnaire to gather data on psoriasis treatment, SARS-CoV-2 infections and related risk factors. Simultaneously, they underwent a blood test to screen for antibodies to SARS-CoV-2 N-antigen. Prevalence of SARS-CoV-2 infections was calculated and logistic regression and Cox proportional-hazards models were performed to determine the association between treatment group and SARS-CoV-2 infection risk, corrected for confounders. Patients with severe COVID-19 disease were described and the mortality rate per treatment group was calculated for the target population. Results Patients were included between April 12 2021 and October 31 2021. Of 551 patients, 59 (10.7% (CI95% 8.3-13.6)) had experienced a SARS-CoV-2 infection, based on questionnaire data combined with serological data. In our study cohort, corrected for confounders, biologic or non-biologic systemic therapy users did not appear to have increased SARS-CoV-2 infection risk compared to patients using other treatment. Only 4 hospitalizations (0.7% (CI95% 0.2-1.0) were reported in our study population and no ICU admissions were reported. The rough mortality rate in the target cohort was 0.32% (CI95% 0.13-0.66) in all treatment groups. Conclusions Corrected for risk-mitigating behavior and vaccination status, a higher SARS-CoV-2 incidence for biologics or non-biologics systemics compared to other treatments could not be proven. Severe cases were infrequent in all treatment groups. This finding further strengthens treatment recommendations that systemic therapies for patients with psoriasis do not require preventive cessation for reduction of SARS-CoV-2 infection risk.